¬PENGARUH SOCIAL MEDIA INFLUENCER TERHADAP PURCHASE INTENTION YANG DIMEDIASI OLEH TRUSTWORTHINESS (STUDI PADA AKUN INSTAGRAM @KULINERSBY) - Purwanto, Albin Sayyid Agnar Caesar; Purwanto, Teguh (Majalah Ekonomi, 2019)
Indonesia is the country with the most monthly active users in Asia Pacific region. This can be an opportunity for businesses to market, promote, or advertise their products through Instagram. Marketers must be smart to find the best way to influence consumers by disguising the advertisements they want to convey so that consumers don’t consider it as noise or interference. This is where the role of influencers is useful, to disguising advertisements. Influencers are "ordinary people" or non-celebrities, who are well-known and focus on certain areas that have thousands of followers on their social media accounts, and people follow or follow because of the fields they are involved in. This study aims to analyze and discuss the influence of social media influencer on purchase intention mediated by trustworthiness on Instagram account @kulinersby. This type of research is conclusive with a quantitative approach. The population is followers of the @kulinersby Instagram account. Questionnaires were distributed to 220 respondents and data were analyzed using path analysis. The results show that there’s a positive and significant influence on social media influencer on trustworthiness on @kulinersby; there’s a positive and significant influence on social media influencer on purchase intentions on @kulinersby; and there’s a positive and significant influence of trustworthiness on the purchase intention on the @kulinersby. There is still an inconsistency between the results of this study and previous research, further research must analyze other variables that might influence purchase intention and analyze other social media other than Instagram.